Foreign Market Network and Internationalization of Domestic Firms: A Panel Data Analysis - Hossain, Md. Shakib (Archives of Business Research, 2025)
The primary focus of this paper is the analysis of how companies create foreign market networks in order to internationalize their domestic businesses. It also aims to identify the current foreign market networks that domestic businesses can use to pursue internationalization as well as the ways in which these networks help local businesses become global. This study makes use of longitudinal quantitative data from 1998 to 2021 from the many Fortune 500 businesses that rose to prominence on the international scene. The paper mostly uses OLS, random effect, fixed effect, poisson regression, prais-winsten, GMM, GEE, GLS, and FGLS methods to determine the outcome. Businesses use a range of common strategies, such as economic development agencies, investment promotion agencies, social networks, and industry groups, exporting, licensing, franchising, joint ventures, wholly-owned subsidiaries, strategic partners, financial institutions, and trade finance providers, supply chain partners, and international trade associations to gain access to distribution channels, reduce risk, facilitate access to market knowledge, and forge relationships with key stakeholders that help them successfully implement their internationalization strategies.